Education and Utilization of Straw as Organic Fertilizer in Mergosingo Village Jatirejoyoso - Melly Amalia Vardia; Siska Ayu Wanda (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This study enhances sustainable agricultural practices by addressing straw waste management issues in Mergosingo Hamlet, Jatirejoyoso village. The aim is to promote the utilization of straw as an organic fertilizer and highlight its relevance within the agricultural sector. Method: Using a qualitative approach, we conducted a one-day educational program for Mergosingo's farming community. Data collected from instructional sessions and discussions were analyzed to explore the adoption of straw as an organic fertilizer for sustainable land management. Practical Applications: This research benefits farmers, practitioners, and policymakers by offering a solution to curb environmental pollution from conventional waste practices. Embracing straw as organic fertilizer could increase crop yields, reduce environmental impact, and improve soil health. Conclusion: This study addresses straw waste and the transition to sustainable agricultural practices. The advocacy for straw's use as organic fertilizer contributes practical insights, advancing agricultural sustainability and environmental awareness.